Creating a Supportive Classroom Environment Through Effective Feedback: Effects on Students’ School Identification and Behavioral Engagement - Monteiro, Vera; Carvalho, Carolina; Santos, Natalie Nóbrega (Frontiers in Education, 2021)
Previous research revealed the connection between students’ behavioural and emotional engagement and a supportive classroom environment. One of the primary tools teachers have to create a supportive classroom environment is effective feedback. In this study, we assessed the supportive classroom environment using the perception shared by all students from the same classroom of teachers' use of effective feedback. We aimed to explore the effect of such an environment on students’ behavioural engagement and school identification. Using a sample of 1188 students from 75 classrooms across 6th, 7th, 9th, and 10th grades, we employed multilevel regression modelling with random intercept and fixed slopes. We explored the effects of both individual perceptions of teachers’ use of effective feedback and the supportive classroom environment on student engagement. The analyses identified that students who perceived that their teachers use more effective feedback had a higher level of behavioural engagement and school identification. Once we controlled the effects of these individual perceptions of teachers’ effective feedback, we still observed the effect of a supportive classroom environment on student engagement. So, in classrooms where teachers used more effective feedback creating a supportive classroom environment, students had higher school identification and behavioural engagement levels, regardless of their individual perceptions of teachers’ feedback. The association between variables remained significant even after controlling students’ characteristics (gender, nationality, mother’s level of education, history of grade retention) and classroom characteristics (grade level, type of school, number of students at grade level). Our findings support the potential of teachers’ feedback practices to foster students’ school identification and behavioural engagement to build a more inclusive school environment and value students’ diversity.